Kenya : Transport Sector Memorandum, Volume 1. Strategy - World Bank (Washington, DC, 2013)
This Memorandum is intended to initiate discussion regarding the appropriate infrastructure strategy and policy direction which will lead to a sustainable transport sector which provides access for people and goods within Kenya and integrates Kenya into the global economy. Unless these two objectives are achieved, the prospects for substantial and continuing social and economic development in Kenya are limired. Large segments of Kenya's population will remain isolated in the rural areas, and the economy will continue as a producer of primary commodities and basic manufactues for domestic and perhaps regional consumption. The report states as the first and most important action to reverse the deterioration in the transport sector, a very major change in the philosophic approach of politicians to the sector is needed. They have to start to treat infrastructure as integral to the economic rather than the political process. Beyond this overarching change in approach, the following should also be considered as needed steps for implementing the strategy: increase private sector investment and management in the ports, airports, railways, and roads systems; reduce the role of the public sector in day-to-day management while retaining core functions for all modes of transportation and increasing public funding; and in terms of financing, rely on performance contracting under either maintenance concessions or long-term performance-based contracts.